Peningkatan Layanan Customer Service Melalui Chatbot Menerapkan Algoritma Text Mining dan TF-IDF - Atmaja, Fajar Surya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Dr. Hospital Pirngadi is a regional general hospital owned by the government and is a type B hospital located in the Medan City area, North Sumatra. Apart from that, Dr. Pirngadi is also a referral hospital for the Medan and surrounding areas. As a regional general hospital, Pirngadi Regional Hospital also plays a role in providing health services for the people of Medan city and its surroundings, services provided by customer service at Dr. Pirngadi Medan City, such as registration and information on patients who wish to register for either inpatient or outpatient care, information regarding doctor's practice schedules, facility service information, patient guarantor cooperation, bad management, and visitor information. Customer service is not yet optimal for patients and visitors, such as limited information provided, lack of accessibility and clarity of information, lack of coordination between various hospital departments. To overcome this problem, customer service can utilize artificial intelligence technology to improve customer service. This research provides a solution by building a system in the form of a chatbot, this chatbot system will become an information medium for patients and visitors. The chatbot development process uses a text mining algorithm for text processing and TF-IDF to give weight to each document available in the database. The system provides responses based on the highest level of similarity, with text mining and TF-IDF algorithms, chatbots can provide precise and accurate information on questions asked by patients and visitors. The final result of this research is a chatbot that can be used by patients and visitors to find out available information. The existence of a chatbot can make it easier for patients and visitors to get information about the services available at Dr. RSUD. Pirngadi, Medan City.